Improving access to free school meals: Evaluating the implementation of free school meal auto-enrolment processes - Rob Oxley; Sundus Mahdi; Louise Padgett; Patience Gansallo; Myles Bremner; Cressida Pidgeon; Annie Connolly; Kate E. Pickett; Bob Doherty; Maria Bryant (PLoS ONE, 2026)
To receive benefits-related free school meals in England, households must currently have an annual household income of less than £7,400 (before any benefits-related income), and parents must submit an application. However, data estimates that ~11% do not apply. This equates to about 215,000 children who could, but do not, receive meals they are entitled to. As schools receive pupil premium funding based on these free school meal allocations, under registrations can impact children, families and the support that schools can offer. Free school meal auto-enrolment is a term to describe the processes by which local governments use welfare datasets to identify and register entitled children, allowing parents an opportunity to opt out should they wish. This process can increase registration uptake, though the current evidence regarding free school meal auto-enrolment is limited. This study aimed to explore factors that influence the successful implementation of free school meal auto-enrolment from a local government perspective. Qualitative data were collected through semi-structured interviews with local government authority representatives and national stakeholders (n = 20) across England, supported by documentary analysis (n = 142 relevant documents). Data were analysed deductively according to the Context and Implementation of Complex Interventions framework. Results revealed there was variation in how local governments undertook and experienced auto-enrolment processes, based on the degree to which it was prioritised, available resources and encountered barriers. Multiple barriers to implementation were described, including capacity, data access and resistance regarding data sharing legalities from information governance colleagues. While barriers could be overcome with adequate leadership support, funding and capacity, the reliance on these conditions may lead to inconsistent auto-enrolment delivery and a lottery in free school meal access across the country.